Humanité des marges et marge de l’humanité : la figure du Lapon dans le paysage anthropologique du XVIIIe siècle - Schnakenbourg, Éric (Presses universitaires de Rennes, 2019)
Lapland was almost unknown in Western Europe until the second half of the seventeenth century. In France, this area and its inhabitants were the subjects of two books which were published in the 1670s, and several others in the second quarter of the eighteenth century. These studies were the roots of a description of the Laplanders who were represented as deformed, superstitious, cowardly, and debauched. With this pejorative image, these people integrated the anthropological reflection which was taking place at that time into the general context: first, of investigation about the hierarchy of humankind and, secondly, of the maturation of the notion of human races. That is why the Laplanders were used as a special feature in the scholarly reflection on the variety of mankind and in the discussions about the single or the multiple origins of Man. From the middle of the eighteenth century onwards, the way of considering the Laplanders began to change, as they were gradually seen with numerous virtues, and thus became increasingly closer to the Noble Savage. In the general context of the Enlightenment, which included a reflection on the organisation of mankind, the Laplanders became symbolic of a specific feature of alterity, in the same way as the recently-discovered inhabitants of other continents.